O humor como estratégia discursiva nas charges do jornal Folha Bancária: uma análise das práticas do Sindicato dos Bancários e Financiários de São Paulo, Osasco e Região durante o período de 2012 a 2017 - Daniel Francisco Bastos Monteiro (2018)
This dissertation aimed to analyze how the humorous discourse in the cartoons of the newspaper Folha Bancária evidences the practices of the Banking and Finance Union of São Paulo, Osasco and Region during the period from 2012 to 2017. For this, among the possibilities of approach about the humor, we opt for the perspective that understands it as a possibility of social criticism, resistance or transgression. In relation to the collection of data, we carried out a preliminary survey of the cartoons through the institutional website of the Union, and then we collected all the cartoons and newspapers in which they were published between 2012 and 2017. The cartoons were organized by themes and grouped in semantic paths. For the analysis of the data, we proposed the construction of a research analytic based on some operative elements and theoretical foundations derived from the foucaultian perspective of discourse and power, as well as on the semiotic analysis model elaborated by Barthes (1990). Regarding the results obtained, from the analysis of the data, we find that the cartoon as a humorous discursive genre is able to approach and diffuse the practices of the Union in a peculiar and disparate way in relation to other formats of communication, being this linked to two reasons the fact that humor is one of the main elements by which it is structured; the presence of cognitive (verbal and visual) resources in the chárgica representation. Such aspects provide the reader with a perspective of reading and unique analytical inputs. In addition, we also observe that some practices of the Union are incongruent and conflicting with the narrative itself defended by the entity. Finally, it is worth emphasizing that, in spite of the fact that the cartoon is configured as a peculiar and relevant communication strategy, it presents some limitations from an analytical point of view, given that, although its content evidences some practices of power and resistance related to the Union, the understanding of the discursive plots and the power relations in which such practices are immersed are not possible to be analyzed only by means of their content. In this way, the unfolding of the selected cartoons and the analysis of some documents that border them, such as the newspapers in which they were published, collective agreements of work and some sources external to the Union were primordial for the enrichment of the empirical data of this research and the reach of the objectives